Abstract Book: First International Conference on Food Security and Sustainable Agri-food Technologies – ICFSSAT 2025 - ICFSSAT 2025 (The North African Journal of Food and Nutrition Research, 2026)
This is the Abstract Book of: First International Conference on Food Security and Sustainable Agri-food Technologies – ICFSSAT 2025. Place: Bejaia, Date: October 14, 15, and 16, 2025 https://icfssat.crtaa.dz